Moralitas Religius Sebagai Kerangka Dasar Membentuk Rumah Tangga Sakinah: Religious Morality as The Basic Framework for The Sakinah Household - ST Sariroh; Mohammad Ali (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
Problems in marriage is one of the problems that most of them are caused by a shallow understanding of religious principles, religious morals about marriage. So it is necessary to have someone who is a role model for all things, especially in the moral and religious aspects, including advice that can dissolve problems, disputes, slander in marriage. Nowadays people are more concerned with worldly values ​​than religious values ​​in carrying out the wheels of household life. Not a few of their households were destroyed because of the crisis of moral and religious values ​​in themselves, so that the desire to form a happy, blessed and peaceful household ran aground in the middle of the road. This paper aims to explain how these household problems can be overcome by the presence of figures/kyai as role models who are obeyed. This research is a type of qualitative research using an empirical approach. As a result of this study, it is stated that through Kyai/characters that couples can imitate consists of 3 main things, First, the clarification approach has the aim of understanding the problems and conditions of couples who need a way out, and also invites couples to realize the wisdom in every problem. Second, how a person can be imitated in both his actions and words in life. Third, the internalization of religious morals which starts from advising, awakening and strengthening the religious knowledge of the couples then being asked to enter a room for each individual couple (husband and wife) so that they can reflect on all things related to their lives, then take them to the right path.